MiR-497 Is Implicated in the Process of Chondrogenesis and Inhibits IHH Gene Expression in Human Chondrocytes. (October 2020) - Zhang, Rui; Cong, Fei; Li, Qi; Min, Zixin; Yan, Jidong; Zhang, Qian; Ma, Jie; Lu, Shemin; Ma, Jianbing
Objective: The aim of this study was to examine differences in microRNA-497 (miR-497) expression during cartilage tissue formation and to test whether miR-497 directly interferes with Indian hedgehog (IHH) gene and inhibits IHH expression in human chondrocytes. Design: At different cartilage development stages and different time points in bone matrix gelatin–induced endochondral ossification (BMG-ECO) rat models, the expression of miR-497 and the Ihh gene was monitored at the mRNA level. Bioinformatic analysis, gene mutation, dual luciferase reporter gene assays and gene expression assays at both the mRNA and protein levels in human chondrocytes were subsequently performed to validate the interaction between miR-497 and the IHH gene. Results: The mRNA expression of miR-497 or the Ihh gene in BMG-ECO rats showed significant differences between the cartilage development stages and between different time points, and the trends in the expression of miR-497 and Ihh were reversed. Bioinformatic and dual luciferase reporter gene assays demonstrated a direct interaction between miR-497 and the IHH gene. Differential mRNA and protein expression profiles of the IHH gene in human chondrocytes after 48 hours of transfection with miR-497 mimics and a negative control indicated that miR-497 inhibited IHH expression. Conclusion: Our study provided new clues for further functional and molecular mechanism studies of miR-497 in chondrogenesis and demonstrated a potential target for clinical therapy for cartilage degenerative disease.